SNAC‐As, stress‐responsive NAC transcription factors, mediate ABA‐inducible leaf senescence. (9th December 2015) - Takasaki, Hironori; Maruyama, Kyonoshin; Takahashi, Fuminori; Fujita, Miki; Yoshida, Takuya; Nakashima, Kazuo; Myouga, Fumiyoshi; Toyooka, Kiminori; Yamaguchi‐Shinozaki, Kazuko; Shinozaki, Kazuo
Summary: Leaf senescence is the terminal phenotype of plant leaf development, and ethylene is a major plant hormone inducing leaf senescence. Recent studies have shown that abscisic acid (ABA) also induces leaf senescence. However, the detailed mechanisms of ABA‐induced leaf senescence remain unclear. We focused on the A subfamily of stress‐responsive NAC (SNAC‐A) transcription factors, the expression of which is induced by abiotic stresses, particularly ABA. Gene expression analysis revealed that seven SNAC‐A genes including ANAC055, ANAC019, ANAC072 / RD26, ANAC002 / ATAF1, ANAC081 / ATAF2, ANAC102 and ANAC032 were induced by long‐term treatment with ABA and/or during age‐dependent senescence. The SNAC‐A septuple mutant clearly showed retardation of ABA‐inducible leaf senescence. Microarray analysis indicated that SNAC‐As induce ABA‐ and senescence‐inducible genes. In addition, comparison of the expression profiles of the downstream genes of SNAC‐As and ABA‐responsive element (ABRE)‐binding protein (AREB)/ABRE‐binding factor (ABF) (AREB/ABFs) indicates that SNAC‐As induce a different set of ABA‐inducible genes from those mediated by AREB/ABFs. These results suggest that SNAC‐As play crucial roles in ABA‐induced leaf senescence signaling. We also discuss the function of SNAC‐As in the transcriptional change of leaf senescence as well as in ABA response under abiotic stress conditions. Significance Statement: Leaf senescence is induced by plant hormones such as ethylene and ABA, but the mechanism for ABA‐induced senescence was still unclear. Here we show that a septuple mutant of SNAC‐A type transcription factors exhibit delayed leaf senescence after ABA treatment, suggesting a critical role in transcriptional control of leaf senescence under abiotic stress.